The Effect of Surgical Start Time on Complications Associated With Neurological Surgeries. Issue 3 (13th October 2017) - Linzey, Joseph R; Burke, James F; Sabbagh, M Amr; Sullivan, Stephen; Thompson, B Gregory; Muraszko, Karin M; Pandey, Aditya S
Abstract: BACKGROUND: Neurosurgical procedures are necessary at all times of day. Other surgical specialties have examined the effect of surgical start time (SST) on morbidity and mortality; however, a similar study has not been performed for neurosurgical procedures. OBJECTIVE: To perform a retrospective cohort study describing the association between SST and operative morbidity. METHODS: We analyzed all patients undergoing neurological surgery between January 1, 2007 and August 1, 2014 at our institution. This study included 15 807 patients. A total of 785 complications were identified through the self-reported morbidity and mortality reports created by faculty and resident neurosurgeons. We used multilevel logistic regression to investigate the association of SST with morbidity. RESULTS: In multilevel logistic regression, our Baseline model demonstrated that the odds of complication increased by more than 50% for start times between 21:01 and 07:00 (odds ratio [OR] 1.53, 95% confidence interval [CI] 1.03-2.29, P = .04). When accounting for the length of the surgery, the odds of a complication were even greater for later time periods 21:01 to 07:00 (OR 2.16, 95% CI 1.44-3.23, P < .001). The only statistically significant factor that predicted severity of the complication was if the operation was emergent compared to elective (OR 1.70, 95% CI 1.11-2.60, P = .02). An SST between 21:01 and 07:00 substantially contributed when severe complications were isolated (OR 1.61, 95% CI 1.50-2.90, P = .08). CONCLUSION: Patients with SSTs between 21:01 and 07:00 are at an increased risk of developing morbidity compared to patients with an SST earlier in the day.